Evaluation of factors related to the success of miniscrew-assisted rapid palatal expansion - Oliveira, Cibele B.; Ayub, Priscila; Angelieri, Fernanda; Murata, Wilson H.; Suzuki, Selly S.; Ravelli, Dirceu B. [UNESP]; Santos-Pinto, Ary (The Angle Orthodontist (EH Angle Education & Research Foundation), 2021)
Objectives: To evaluate whether the success of miniscrew-assisted rapid palatal expansion (MARPE), performed in patients with advanced bone maturation is related to factors such as midpalatal suture (MPS) maturation, age, sex, or bicortical mini-implant anchorage. Materials and Methods: Twenty-eight cone beam computed tomography (CBCT) scans of adults and post-pubertal adolescents treated by MARPE were included in the sample. CBCT images before (T0) and after expansion (T1) were used to evaluate the skeletal changes and the success or failure of MARPE. Axial images of MPS were extracted from T0 and classified into one of the five maturation stages. The correlation between MARPE success and the factors of age, sex, MPS maturation, and bicortical mini-implant anchorage was investigated. Results: Only the age showed a statistically significant negative correlation with MARPE success and all the skeletal measures. There was an 83.3% success rate among individuals aged 15 to 19 years, 81.8% from 20 to 29 years, and 20% from 30 to 37 years. MPS maturation showed a negative correlation with the expansion effect. Subjects with stages B or C of MPS maturation showed a 100% success rate, followed by stage D (62.5%) and stage E (58.3%). Conclusions: As age increased, there was a decrease in MARPE success and the skeletal effects of maxillary expansion. Sex and bicortical mini-implant anchorage were not shown to be relevant factors. There was no correlation between MPS maturation and MARPE success; however, it was observed that all cases of MARPE failure were classified as stage D or E of MPS maturation. (Angle Orthod. 2021;91:187-194.).
Keywords: Maxilla; Midpalatal suture maturation; Palatal expansion